2016
DOI: 10.1371/journal.pone.0168384
|View full text |Cite|
|
Sign up to set email alerts
|

Dynamic Changes of Soil Surface Organic Carbon under Different Mulching Practices in Citrus Orchards on Sloping Land

Abstract: Mulching management has been used in many places all over the world to improve agricultural sustainability. However, the cycling of carbon in the soil under applications of mulch on sloping arable land is not yet fully understood. A four-year field experiment was carried out in Xiaofuling watershed of Danjiangkou reservoir in China. The object was to evaluate the effects of the application of straw mulch (ST) and grass mulch (GT) on dynamic changes in soil organic carbon and its fractions. Results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 53 publications
(62 reference statements)
4
29
0
Order By: Relevance
“…DOC concentrations can be used as an indicator of substrate availability of readily available C and NO 3 − concentrations for denitrification [33]. Gu et al [44] found higher DOC (~23%) in the first 40 cm of soil of an established citrus orchard growing in a sandy loam soil covered with grass versus bare soil. They suggested that higher DOC could be responsible for the growth of vegetation, reduction of soil temperatures, and evaporation of water.…”
Section: Total N Concentration and C/n Ratio In Leavesmentioning
confidence: 99%
“…DOC concentrations can be used as an indicator of substrate availability of readily available C and NO 3 − concentrations for denitrification [33]. Gu et al [44] found higher DOC (~23%) in the first 40 cm of soil of an established citrus orchard growing in a sandy loam soil covered with grass versus bare soil. They suggested that higher DOC could be responsible for the growth of vegetation, reduction of soil temperatures, and evaporation of water.…”
Section: Total N Concentration and C/n Ratio In Leavesmentioning
confidence: 99%
“…Mulching is among the simplest and widely used technique for soil water conservation in agricultural lands. It involves covering soil surface with a layer of organic materials for purpose of reducing soil moisture loss through evaporation [114,115]. Additionally, mulching has a number of cobenefits in crop fields, such as the addition of organic matter and suppression of weeds [116,117].…”
Section: Mulching Applicationmentioning
confidence: 99%
“…The content of POC with inorganic fertilizer was lower (16-21%) than that in organic fertilizer application (Table 4). Based on their research in a typical subtropical climate, Hubei Province of Central China, Gu et al, (2016) reported that the application of straw mulch and grass mulch on the soil surface increased significantly the contents of SOC and POC fraction in the soil. Compared to control treatment, the increases of POC in grass mulch and straw mulch treatments in the 0±40 cm soil layer were 54.46% and 37.18% respectively, while the use of straw mulch and grass mulch increased SOC by 15.15% and 21.14% respectively.…”
Section: Effect Of Land Use and Management Practices On Soil Organic mentioning
confidence: 99%